The Superiorly Based Partial Rectus Abdominis and External Oblique Flap for Lower Pole Coverage in Prosthetic Breast Reconstruction: A Prospective Cohort Study of 47 Consecutive Flaps. Issue 5 (November 2020) - Lam, Quoc (Tai Khoa); Nowicki, Jake; Crittenden, Tamara; Howes, Benjamin H.L.; Dean, Nicola R.
Abstract : Background: This study evaluated health related quality of life and morbidity in patients who had a superiorly based partial rectus abdominis and external oblique (SPREO) flap for lower pole coverage as a component of 2-stage prosthetic breast reconstruction. Methods: A prospective cohort study of patients undergoing immediate and delayed 2-stage breast reconstruction including a SPREO flap for lower pole coverage was conducted. The BREAST-Q and a study-specific questionnaire were used to determine outcomes after this procedure. BREAST-Q questionnaires were completed preoperatively and postoperatively and compared with normative values. Results: BREAST-Q questionnaires were completed by 27 women. The mean patient age was 54.3 ± 9.6 years. Mean BREAST-Q scores improved significantly between preoperative and postoperative time points in Satisfaction with Breasts (preoperative 43.2 ± 26.9, postoperative 66.2 ± 19.5, P = 0.001) and Psychosocial Wellbeing (preoperative 59.4 ± 16.4 postoperative 75.5 ± 19.4, P = 0.002). Mean scores were not significantly different in the domains Physical Wellbeing Chest, Physical Wellbeing Abdomen and Sexual Wellbeing. Postoperative BREAST-Q scores were significantly higher ( P < 0.05) than previously published normative scores in Satisfaction with Breasts. Conclusions: This study reports the use of the SPREO flap for lower pole coverage in 2-stage prosthetic breast reconstruction and demonstrates that it may be a useful addition to the existing repertoire of flaps used in breast reconstruction.